The Effect of Complex Training on Some Anaerobic Abilities’ Indicators in Soccer Players Aged (18) Years Old - Abid, Haider; Ali, Abaas (Journal of Physical Education, 2020)
The research aimed at designing complex trainings in soccer as well as identifying the effect of these trainings on some anaerobic abilities in soccer players. The researchers hypothesized statistical differences between pre and posttests for both experimental and controlling groups in some anaerobic abilities’ indicators in soccer players aged (18) years old in favor of the posttests. In addition to that, they hypothesized statistical differences in groups in anaerobic abilities indicators in soccer players aged (18) years old in favor of the experimental group. The researchers used the experimental method and the training was applied on (20) soccer players from Al Aeen Athletic club season (2018 – 2019) aged (18) years old. The training was applied for (8) weeks including 24 training sessions with 3 sessions per week to concluded improvement in anaerobic abilities understudy.